The effect of mentha cordifolia opiz (yetba buena) on the somato sensory evoked potentials of adult male albino rats - Sanchez, Mario G.
A three-phase investigation was conducted to study the effects of yerba buena (Mentha cordifolia. Opiz.) on the somasensory evoked potentials in adult male albino rats. The subjects were randomly allocated to either the experimental or the control group. Experimental animals in the first two sets of experiments were given the herbal drug via an orogastric tube while the control received 10% starch solution. In the first place, the evoked potentials were recorded every thirty minutes for four hours. Peak latencies and peak amplitudes of P2 were measured and plotted against time. The amplitude curve of the experimental group was significantly different from that of the controls. The decrement was maximal ninety minutes after administration of the herbal drug. Latency changes were not significant. The observed changes maybe related to the analgesic effect of yerba buena. Results obtained in the second phase was consistent with that of phase I, that is, a reduction in amplitude of the revoked responses following administration of yerba buena. When naloxone was administered the amplitude of the evoked responses was restored to and even exceeded baseline values. Reversal by naloxone suggests an opioid-mediated mechanism for the herbal drug-induced analgesia. To determine whether the opioid antagonist by itself affects the somatosensory evoked potentials, naloxone was given to the experimental group while the controls received NSS. Naloxone has no intrinsic effect either on the latency or amplitude of the evoked responses.
Thesis--(MS in Physiology) University of the Philippines Manila
Keywords: Plants, Medicinal; Medicine, Herbal